Sistem Otomasi Penyiraman Bibit Tanaman Berbasis Programmable Logic Controller (PLC) - Dwirgo Sahlinal; Zuriati Zuriati; Dewi Kania Widyawati (Jurnal Ilmiah ESAI, 2007)
The watering of plants seeds could be carried out automatically by using technology development of Programmable Logic Controller (PLC). PLC is a control system that can be programmed in controlling and organizing the watering of plants seeds. It is also can be arranged according to the need of water in each step of seed growth until the plants completed mature. By using sensor to measure the water humidity and timing program to organize water pump in controlling watering process so that the seeds are not water accessed, therefore the seeds growth could be optimal.Â Kata Kunci:Â  PLC, penyiraman bibit tanaman